Influence of religion and gender on the birth control attitude among young adults - George, Nimmi; Joseph, Justin; Mathew, Anitta (Journal of Social Review and Development, 2023)
The prime objective of the study was to evaluate the attitude of the young couple towards the family planning and the influencing factors of the religion and gender on it. Questionnaire method was used to collect data from 305 participants including Females (N=226) and Males (N=79) in the age group of 18-26 from southern and central Kerala. Convenient sampling method was used by the researcher to select participants. The study revealed that religion and gender have an influence on the family planning among young adults.